KAJIAN KOMUNIKASI MASSA PADA SURAH AL-HUJURAT AYAT 6 - Arifin Arifin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
The mass media, as an integral part of life, has become a blessing as well as a challenge to human life in the information society era. No exception for Muslims who live and become part of the information society at this time. The holy Qur’an which is believed to be the guide of life throughout the ages should be understood and explored by various disciplines of science. The universal values in the Qur’an can not only be highlighted by the doctrinal and theological perspectives of the norm, but also with the point of view of social science, one of them with the approach of mass communication. This paper explores surah Al-Hujurat verse 6 then explores it with a mass communication study approach. From the results of exploratioining and understanding to the interpretation of the scholars on surah Al-Hujurat verse 6 and various literature on mass communication, especially in mass media studies, it can be concluded that Surah Al-hujurat verse 6 contains various values and knowledge of how to respond the mass media today, The concept of knowing the news carrier, Tabayyun’s attitude, and the attention to the impact of the news in this chapter is in harmony with the study of mass communication in which there are theories about criticism of media, media texts and the effects of the mass media.